2021
DOI: 10.2533/chimia.2021.18
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Blended Learning for Foundation Year Chemistry Students

Abstract: The chemistry foundation year at the University of East Anglia is a diverse cohort with a wide range of prior educational experience and confidence levels. A flexible learning program combining extensive online materials intended for asynchronous study and face to face peer instruction is provided. Study is divided into weekly topics. Students are directed to take a short introductory quiz at the beginning of the week, feedback on which allows them to tailor the extent of asynchronous learning to their own ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…1; red ovals). These findings are consistent with prepandemic observations by Chamberlain et al (2021) who reported that a general decline in student engagement occurred over the semester in a large general chemistry course.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1; red ovals). These findings are consistent with prepandemic observations by Chamberlain et al (2021) who reported that a general decline in student engagement occurred over the semester in a large general chemistry course.…”
Section: Resultssupporting
confidence: 91%
“…Other students indicated that they were seeking more resources and support to understand content or identified the need for more practice questions. In another study, a similar observation was reported, where some of the students expressed their desire to see additional resources, seemingly contradicting the picture of declining engagement over the course of the semester (Chamberlain et al, 2021).…”
Section: Resultsmentioning
confidence: 75%
“…This is especially a problem for freshmen, who generally have not learned how to achieve such self-regulation. A solution for this problem can be found in blended learning, which facilitates student engagement in active learning. Moreover, blended learning approaches enable students to adapt a course to their learning needs provided that enough opportunities for flexibility, feedback, and self-assessment are available. , Despite this, blended learning, and other recommended teaching approaches in general, hardly reach higher education practice. The problem is that a teacher’s teaching practice is typically set against an ideal change proposal which is generally unattainable due to practical constraints that emerge from the work context.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, blended learning is more attuned to current and future generations of students, as it employs online educational technologies and might thereby enhance student motivation and participation . Indeed, multiple efforts have been or are underway in the chemistry community to implement blended and flipped learning approaches. Based on the literature we conclude that blended learning may provide an appropriate basis for engaging students in active learning, supporting self-directed learning and developing the desired academic study skills and attitudes. , …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation